Maternal and community factors associated with unmet contraceptive need among childbearing women in Northern Nigeria - Bola Lukman Solanke; Funmilola Folasade Oyinlola; Olaoye James Oyeleye; Benjamin Bukky Ilesanmi (Contraception and Reproductive Medicine, 2019)
Abstract Background Unmet need for modern contraceptive remains a critical reproductive health challenge in Nigeria. Numerous studies in Nigeria and other countries have investigated the patterns, prevalence and associated factors of unmet contraceptive need. In spite of these, the associated factors of unmet contraceptive need in Northern Nigeria have remained insufficiently explored. The few studies that focused on Northern Nigeria have mainly examined maternal individual factors leaving out higher level factors such as community-level factors that may be associated with unmet contraceptive need. This study examines the extent to which maternal and community factors are associated with unmet contraceptive need in Northern Nigeria. Method Data was pooled from 2008 to 2013 Nigeria Demographic and Health Surveys. A weighted sample size of 26,730 women was analysed. The outcome variable was unmet contraceptive need, dichotomised into no unmet need and unmet need. The explanatory variables were individual maternal characteristics such as age, education, number of living children, age at marriage, pregnancy termination experience, and death of a child, and selected community characteristics such as community socioeconomic status, community literacy level, community knowledge of modern contraceptive and geo-political zone. The Multilevel Logistic Regression Model (MLRM) was applied. Result Results showed a prevalence of 18% unmet contraceptive need among Northern women in Nigeria. Maternal age of 35 years or older (AOR = 0.873; p < 0.05, CI: 0.780–0.976), having five or more living children (AOR = 1.813; p < 0.001, CI: 1.663–1.977), higher maternal education (AOR = 0.787; p < 0.05, CI: 0.625–0.993), and never experience death of a child (AOR = 0.866; p < 0.001, CI: 0.805–0.933) are the maternal factors significantly associated with unmet contraceptive need, while high community literacy level (AOR = 1.230; p < 0.05, CI: 1.041–1.454), moderate (AOR = 0.862; p < 0.05, CI: 0.767–0.968) or high (AOR = 0.821; p < 0.05, CI: 0.726–0.929) community knowledge of modern contraceptive, and geo-political zone of residence are the community-level characteristics significantly associated with unmet contraceptive need among women in Northern Nigeria. Conclusion Maternal and community factors are significantly associated with unmet contraceptive need, but based on the ICC maternal factors have more significance in Northern Nigeria. The expansion of existing family planning delivery points to cover all communities including rural and remote areas in the region is imperative.